To solve the system of equations using the elimination method, we have:
- \( y = x^2 + x - 42 \) (quadratic equation)
- \( y = -x + 6 \) (linear equation)
First, we can set the two equations equal to each other since they both equal \( y \):
\[ x^2 + x - 42 = -x + 6 \]
Now, let's rearrange this equation:
\[ x^2 + x + x - 42 - 6 = 0 \] \[ x^2 + 2x - 48 = 0 \]
Next, we will factor the quadratic equation \( x^2 + 2x - 48 = 0 \).
To factor, we need two numbers that multiply to \(-48\) and add up to \(2\). These numbers are \(8\) and \(-6\). So we can rewrite the equation as:
\[ (x + 8)(x - 6) = 0 \]
Setting each factor to zero gives us:
- \( x + 8 = 0 \) \( \Rightarrow x = -8 \)
- \( x - 6 = 0 \) \( \Rightarrow x = 6 \)
Now that we have \( x \) values, we can find the corresponding \( y \) values using the second equation \( y = -x + 6 \).
For \( x = -8 \): \[ y = -(-8) + 6 = 8 + 6 = 14 \] So, one solution is \( (-8, 14) \).
For \( x = 6 \): \[ y = -(6) + 6 = -6 + 6 = 0 \] Thus, the second solution is \( (6, 0) \).
The solutions to the system of equations are:
- \( (-8, 14) \)
- \( (6, 0) \)
Now, looking at your responses:
- \( (8, -2) \) and \( (-6, 12) \)
- \( (6, 0) \)
- \( (-8, 14) \)
- \( (-8, 14) \) and \( (6, 0) \)
The correct answer is:
\( (-8, 14) \) and \( (6, 0) \).